Pharmacology and biochemistry undergraduate students'concern for a healthy diet and nutrition knowledge - Bernardes Spexoto, Maria Claudia [UNESP]; Ferin, Giovana Garcia [UNESP]; Duarte Bonini Campos, Juliana Alvares [UNESP] (Aula Medica Ediciones, 2015)
Objective: To estimate the concern for a healthy diet and the nutrition knowledge of undergraduate students of a pharmacology and biochemistry program and their associations with the variables of interest.Methods: This cross-sectional study administered the Nutrition Knowledge Scale and the How is your diet? questionnaire to 381 students. The associations between concern for a healthy diet and nutrition knowledge and between these two factors and the demographic variables were measured by the chi-square test (chi(2)) or Fisher's exact test. The significance level was set at 5%.Results: The mean age of the students was 20.6 (standard deviation [SD] = 2.7) years; 78.2% were female students; their mean body mass index was 22.6 (SD = 3.7) kg/m(2); and 73.5% had an appropriate body mass index related nutritional status. Most students fell within the category "pay attention to your diet" (77.1%) and "moderate nutrition knowledge" (79.7%). Concern for a healthy diet was significantly associated with program year (p = 0.024), socioeconomic class (p = 0.012), and physical activity (p < 0.001). Nutrition knowledge was associated only with program year (p < 0.001). Concern for a healthy diet was not associated with nutrition knowledge (p = 0.808).Conclusion: Physically inactive, first-year students from socioeconomic class B (US$ 1,046 - 1,872) were less concerned with a healthy diet. Such concern was not related to the students'nutrition knowledge.

Objetivo: Estimar la preocupación por una alimentación sana y el conocimiento de la nutrición de los estudiantes de un título de grado en Farmacia y Bioquímica y su asociación con variables de interés. Métodos: Este estudio transversal. Participaron 381 estudiantes. Fue utilizado como instrumentos de medición a “Escala El conocimiento nutricional” y “¿Cómo está la comida?”. Se realizó un estúdio asociación entre la preocupación por una alimentación sana y el conocimiento nutricional y aquellos con las variables demográficas mediante el uso de la prueba de chi-cuadrado (2) o Fisher. Hemos adoptado un nivel de significación del 5%. Resultados: La edad promedio de los estudiantes fue de 20,6 (SD = 2,7) años, el 78,2% eran varones femenina. El índice de masa corporal (IMC) fue de 22,6 (SD = 3,7) kg/m2 y 73,5% se presentaron con un estado nutricional adecuado para este indicador. La mayoría de los alumnos evaluados fueron categorizados como “estad atentos con la comida” (77,1%) y “el conocimiento nutricional moderado” (79,7%). Se han observado asociaciones significativas entre la preocupación por una alimentación sana y año del curso (p = 0,024), la classe económica (p = 0,012) y la actividad física (p < 0,001). El conocimientos nutricionales sólo se asoció con el año del curso (p < 0,001). No se encontró asociación significativa entre la preocupación por una alimentación saludable y conocimientos sobre nutrición (p = 0,808). Conclusión: Los estudiantes de primer año por supuesto, pertenecen a la clase económica B y no físicamente activos mostraron una menor preocupación por una alimentación saludable. Esta preocupación no se estaba relacionado con el conocimiento nutricional presentado por los estudiantes.
Preocupación por una alimentación sana y el conocimiento de la nutrición de los estudiantes de un título de grado en farmacia y bioquímica
Keywords: Biochemistry students; Healthy behaviors; Healthy foods; Nutrition knowledge; Pharmacology students; Estudiantes de Bioquímica; Comportamientos Saludables; Los alimentos saludables; Conocimientos de Nutrición; Estudiantes Farmacia